The Usage of 5G Technologies for the Purpose of Business Improvement (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The subject of this paper is to investigate the impact of 5G technologies usage on business improvement. The main is to analyse the attitudes, perceptions, and degree of acceptance of the application of 5G technologies. The main hypothesis was to confirm that with a high degree of acceptance of 5G technologies, the conditions for business improvement will be created. The primary research was conducted with a questionnaire on a sample of 122 respondents, and the main hypothesis is that the high level of acceptance of 5G technologies creates prerequisites for business improvement. In addition to the basic hypothesis, additional hypotheses were set: Knowledge of 5G technologies positively affects attitudes about the impact of 5G technologies, and perceived skill in using 5G technologies affects the perceived usefulness of 5G technologies in business. Based on the research results, it can be confirmed that the acceptance of the use of 5G technologies has a positive effect on business and collaboration. Also, there is a positive connection between the perceived skill of using 5G technologies and the perceived usefulness of 5G technologies in business, as well as a positive connection between knowledge of 5G technologies and the attitude about the impact of 5G technologies.